Pengaruh Overconfidence , Risk Perception dan Self-Control Terhadap Keputusan Investasi Cryptocurrency - Fachry Rahmatullah Aditama; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2023)
The purpose of this study was to determine whether overconfidence, risk perception and self-control affect cryptocurrency investment decisions. This research design uses quantitative methods in this study to collect primary data. This study used a purposive sampling method and the number of respondents was 76 people who had invested in cryptocurrency. The results of the research based on hypothesis testing on the t test show that the first hypothesis (H1) states that overconfidence has a positive and significant effect on decisions. The results of this study show that overconfidence has a positive and significant effect on cryptocurrency investment decisions. risk perception has no effect on the decision. The results of this study show that risk perception has no effect on cryptocurrency investment decisions. Stating that Self-Control has a negative and significant effect on cryptocurrency decisions.Keywords: Overconfidence, risk perception, self-control, cryptocurrency investment